COVID-19 and its implications on male and female fertility: future impacts (Research, Society and Development, 2022)
In recent years, the COVID-19 has been the focus of studies, widely explored by specialists from different areas, involving different research potentials due to the viral tropism for receptors in human body systems. Angiotensin-Converting Enzyme 2 (ACE2) is considered the main viral gateway, being located in different tissues and organs, allowing SARS-CoV-2 to affect various parts of the human body, including the reproductive system. The aim of this integrative review is to investigate the effects caused by the parhogenicity of the SARS- CoV-2 virus on reproductive system involving fertility. Thus, the question arises of the possibility that the virus promotes infertility due to the presence of ACE2 in the reproductive system, and the need to identify the possible effects that the virus can trigger. Studies indicate that in the female reproductive system, it was observed in post-infected patients: premature ovarian failure, involvement and damage of granulosa cells and ovarian tissues, alteration of the menstrual cycle, and hormonal alterations. About the male reproductive system, negative impacts were identified, such as the involvement of Sertoli cells and a decrease in Leydig cells, changes in hormone levels, reduction in the quantity and quality of sperm, leukocyte infiltrate in the testicular interstitial, orchitis, thickening basement membrane, destruction of germ cells and fragmentation of sperm DNA. Despite research indicating the possible damage caused by SARS-CoV-2 to the male and female reproductive system, there is a need for more theoretical and practical studies, which prove, through underlying mechanisms, the possible future impacts after viral infection on human fertility.